(untitled) (Colombia Medica, 1987)
The multiplicity of drugs that have been used for the treatment of malaria is a clear indication of the formidable problem imposed by drug-resistant malaria. The advent of new biochemical and pharmacological tools and the development of a system for in vitro culture of plasmodial compounds in search of antiplasmodial activity. Of these two groups of drugs, sesquiterpene lactones and amino alcohols appear to have more significant antimalarial potential. What follows is an account of the most recent developments in antimalarial therapy.